Cultural group selection in the light of the selection of extended behavioral patterns. (9th March 2016) - Simon, Carsta
Abstract: The cultural group selection hypothesis is supported by considerations of short-term and long-term behavioral patterns of group members, and the short-term and long-term consequences of that behavior. The key to understanding cooperation lies in understanding that the effect of an extended behavioral pattern does not equal – and might even be opposite to – the added effects of its parts.